Pneumococcal BgaA Promotes Host Organ Bleeding and Coagulation in a Mouse Sepsis Model - Takemura, Moe; Yamaguchi, Masaya; Kobayashi, Momoko; Sumitomo, Tomoko; Hirose, Yujiro; Okuzaki, Daisuke; Ono, Masayuki; Motooka, Daisuke; Goto, Kana; Nakata, Masanobu; Uzawa, Narikazu; Kawabata, Shigetada (Frontiers in Cellular and Infection Microbiology, 2022)
Streptococcus pneumoniae is a major cause of invasive diseases such as pneumonia, meningitis, and sepsis, with high associated mortality. Our previous molecular evolutionary analysis revealed that the S. pneumoniae gene bgaA, encoding the enzyme β-galactosidase (BgaA), had a high proportion of codons under negative selection among the examined pneumococcal genes and that deletion of bgaA significantly reduced host mortality in a mouse intravenous infection assay. BgaA is a multifunctional protein that plays a role in cleaving terminal galactose in N-linked glycans, resistance to human neutrophil-mediated opsonophagocytic killing, and bacterial adherence to human epithelial cells. In this study, we performed in vitro and in vivo assays to evaluate the precise role of bgaA as a virulence factor in sepsis. Our in vitro assays showed that the deletion of bgaA significantly reduced the bacterial association with human lung epithelial and vascular endothelial cells. The deletion of bgaA also reduced pneumococcal survival in human blood by promoting neutrophil-mediated killing, but did not affect pneumococcal survival in mouse blood. In a mouse sepsis model, mice infected with an S. pneumoniae bgaA-deleted mutant strain exhibited upregulated host innate immunity pathways, suppressed tissue damage, and blood coagulation compared with mice infected with the wild-type strain. These results suggest that BgaA functions as a multifunctional virulence factor whereby it induces host tissue damage and blood coagulation. Taken together, our results suggest that BgaA could be an attractive target for drug design and vaccine development to control pneumococcal infection.